Analysis of senescence in gingival tissues and gingival fibroblast cultures. Issue 4 (2nd May 2022) - Furukawa, Masae; Matsuda, Kazunari; Aoki, Yu; Yamada, Mitsuyoshi; Wang, Jingshu; Watanabe, Maki; Kurosawa, Mie; Shikama, Yosuke; Matsushita, Kenji
Abstract: Objective: To determine senescence‐associated changes in the gingival tissues of aged mice and gingival fibroblast cultures. Materials and Methods: The production of senescence‐associated β‐galactosidase (SA‐β‐gal) and mRNA expression of p16, p21,  interleukin (IL)‐1β, and tumor necrosis factor α (TNF‐α) were evaluated in gingival tissues, gingival fibroblasts of 10‐ and 20‐month‐old C57BL/6NCrl mice, and multiple‐passaged and hydrogen peroxide‐stimulated human gingival fibroblasts (HGFs). Changes in molecular expression in HGF cultures due to senescent cell elimination by the senolytic drug ABT‐263 (Navitoclax) were analyzed. Results: Compared to 10‐week‐old mice, the 20‐month‐old mice had higher numbers of M1 macrophages. The proportion of cells expressing SA‐β‐gal were also higher in 20‐ month‐old mice than in 10‐week‐old‐mice. Gingival fibroblasts in 20‐month‐old mice expressed less collagen 1a1, collagen 4a1, and collagen 4a2 mRNA than those in 10‐week‐old mice. Compared to control cells, H2O2 treated HGF cells expressed higher levels of SA‐β‐gal and p16, p21, IL‐1β, and TNF‐α. Furthermore, ABT‐263 suppressed HGF cell expression of cytokines after senescence induction. Conclusions: Senescence‐associated changes were observed in the gingival tissues of aged mice and HGF cultures. In addition, the potential of senolytic drugs to modify aging‐related changes in the gingiva was shown.